Evaluation of effective parameters for the synthesis of poly(propylene fumarate) by response surface methodology. Issue 20 (24th May 2014) - Shahbazi, Sara; Jafari, Yaser; Moztarzadeh, Fathollah; Mir Mohamad Sadeghi, Gity
ABSTRACT Poly(propylene fumarate) (PPF) is an unsaturated linear polyester, which was synthesized for potential applications in filling skeletal defects. The synthesis was carried out according to a two‐step polymerization reaction. In this research, a functional relationship among three reaction factors [temperature, reaction time, and stoichiometry of the monomers] in the PPF synthesis was established by responses of the surface methodology/central composite design (CCD). After that, on the basis of the responses of CCD [increasing intensity ratio of the CH/OH peaks in Fourier transform infrared (FTIR) spectra], designed substances were synthesized and analyzed by FTIR spectroscopy. The synthesized PPF, based on the optimized synthesis conditions from CCD, had a high molecular weight, low hydroxyl group content, and optimum viscosity. According to the CCD response, the best product was obtained through with a molar ratio of diethyl fumarate/propylene glycol/ZnCl2/hydroquinone of 1:3.5:0.01:0.002 and a 17‐h reaction time at 140°C. Eventually, the synthesized PPF was characterized by FTIR spectroscopy, NMR, and gel permeation chromatography analyses. © 2014 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2014, 131, 40932.